Volatility and co-movements of the equity markets in Central Europe: Evidence from Poland and Hungary - Anna Chmielewska (Economic and Environmental Studies (E&ES), 2018)
This article aims at verifying if there has been a structural change in the co-movement pattern of selected Central and Eastern Europe (CEE) over the ten-year period following the financial crisis. The empirical results confirmed that such a change was observed both in the correlation and volatility levels for specific market segments, as well as in the market dynamics. These findings provide a new insight into understanding the shock resilience, which consequently can supplement a wider assessment of the systemic risk in the financial markets. The key results point towards a decreased uncertainty in estimated correlation levels during the post-crisis period. Such findings are consistent with the hypothesis that intermarket linkages are currently better reflected in market prices when compared to the pre-crisis period. While this is clearly a positive signal for future system stability, it also evidences that the widely used GARCH and DCC specifications turn to be relatively narrow and therefore greater caution is highly recommended when interpreting estimation results.
Keywords: G15; C58; G17; G01; D53; 330; correlation; volatility; financial markets; GARCH; financial econometrics; systemic risk; CEE